INVERS MATRIKS TOEPLITZ BENTUK KHUSUS nxn (n>3) DENGAN MATRIKS BLOK 2x2 - Rahma, Ade Novia; Irawan, Teddy; Rahmawati, Rahmawati; Sukmawati, Sri (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
In this paperl, we will discuss inverse of a special form Toeplitz matrix with a block 2 x 2matrix which has two submatrix that are invertible through the application of Schur Complement, there are several steps to determine the inverse of a Toeplitz matrix. The results obtained rae obtaining the invertible form of submatrix invers of the Toeplitz matrix and the general form of the inverse matrix of the special form Toeplitz matrix ,  with 2 x 2 block matrix.